Islamic Business Ethics in Fiqh on the Transaction of Corn Crops by Estimation System in Nagari Sumanik, Salimpaung District, Tanah Datar Regency - Taufik Hidayat; Ardiles Admi; Ari Yonata; Eldaneti Eldaneti; Reni Siska; ⁠Siti Asiyah Nasution (ARRUS Journal of Social Sciences and Humanities, 2024)
Muamalah is a human activity that cannot be separated from life, which aims to obtain income and fulfil life's needs in order to achieve a better life. The Principles of Islamic Business Ethics was analyzed to find how it affects the income earned by farmers. It aims to add to the khazanah literature in the field of muamalah in particular. One of them is the trade relationship (buying and selling), which is encountered in daily life. Buying and selling activity is a form of muamalah transaction recommended by Islam. People often do it easily, without knowing whether the buying and selling transactions carried out are contrary to muamalah fiqh. Therefore, in its process, the pillars and conditions must be fulfilled to avoid voiding and damaging the transaction as happened in the practice of buying and selling corn by estimation in Nagari Sumnaik. The objectives of this study are to find out the buying and selling process, its practice, and the Islamic Business Ethics perspectives of muamalah fiqh on buying and selling corn with the estimation system. The method used descriptive qualitative sourced from primary and secondary data. Data collection techniques were through interviews, documentation, observation. The data analysis method used qualitative descriptive analysis. The results of this study indicated that the buying and selling process of corn with estimation system in Nagari Sumanik is not valid because there are conditions that are not fulfilled according to Islamic provisions, as well as the unfair element of compulsion in setting prices and not given the right khiyar if something unwanted happens in the estimation buying and selling transaction.